1967
DOI: 10.1002/pssb.19670210125
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Quadrupole Interaction of 23Na and 11B and the Crystal Structure of NaBF4

Abstract: The nuclear quadrupole interaction of *3Na and llB in NaBF, is investigated between 23 and 260 "C using single crystals and crystalline powder respectively. At 23 "C the folbwing results are found: e2 q Q/h (ZJNa) = 1008.4 kHz; e2 q Q/h ("B) = 59.9 kHz; r] (Na) = = 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1970
1970
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Klinkenberg further reports that NaBF, (and by inference, NaBF30H) crystallizes in the orthorhombic system, space group Cmcm and is isomorphous with NaCIO,. This result for NaBF, has since been verified (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 57%
“…Klinkenberg further reports that NaBF, (and by inference, NaBF30H) crystallizes in the orthorhombic system, space group Cmcm and is isomorphous with NaCIO,. This result for NaBF, has since been verified (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 57%
“…A structural phase transition in NaBF4 has been reported by Amirthalingam et al (1980) using differential scanning calorimetry, optical microscopy and X-ray techniques. They concluded that the low temperature orthorhombic phase transforms into a rhombohedral phase above 535 K, supporting the earlier ^^B and ^^Na NMR results (Weiss and Zohner, 1967). Pistorius et al (1969) have studied the phase diagram of NaBF4 at high pressures and temperatures employing DTA methods.…”
mentioning
confidence: 70%